2000
DOI: 10.1111/j.1749-6632.2000.tb06370.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Abnormalities in Energy Metabolism in Alzheimer Disease: Interaction with Cerebrovascular Compromise

Abstract: Alzheimer disease (AD) is a form of the dementia syndrome. AD appears to have a variety of fundamental etiologies that lead to the neuropathological manifestations which define the disease. Patients who are at high risk to develop AD typically show impairments of cerebral metabolic rate in vivo even before they show any evidence of the clinical disease on neuropsychological, electrophysiological, and neuroimaging examinations. Therefore, impairment in energy metabolism in AD can not be attributed to loss of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(92 citation statements)
references
References 114 publications
(286 reference statements)
4
88
0
Order By: Relevance
“…196 Furthermore, co-culturing neurons with astrocytes pre-treated with A␤ significantly decreased neuronal survival as compared with co-culturing with naive astrocytes. 196 Analysis of the activity of metabolic enzymes similarly yielded controversial results: both decrease 197,198 and increase 195,199 in the activity of enzymes associated with glucose metabolism have been reported in AD brain preparations. These discrepancies may reflect opposite cell-specific changes in glucose metabolism developing at different stages of AD.…”
Section: Metabolic Remodeling Of Astroglia In Admentioning
confidence: 99%
“…196 Furthermore, co-culturing neurons with astrocytes pre-treated with A␤ significantly decreased neuronal survival as compared with co-culturing with naive astrocytes. 196 Analysis of the activity of metabolic enzymes similarly yielded controversial results: both decrease 197,198 and increase 195,199 in the activity of enzymes associated with glucose metabolism have been reported in AD brain preparations. These discrepancies may reflect opposite cell-specific changes in glucose metabolism developing at different stages of AD.…”
Section: Metabolic Remodeling Of Astroglia In Admentioning
confidence: 99%
“…Previous studies have suggested that a decrease in brain bioenergetics may be a useful biomarker to predict disease decades before symptoms [33][34][35][36]. Decreases in mitochondrial bioenergetics, metabolic enzyme expression and activity, cerebral glucose metabolism, along with increased oxidative stress, Aβ deposits within mitochondria, and expression of ABAD are associated with the prodromal state of AD [34,[37][38][39][40][41][42].…”
Section: Current Strategies Targeting Mitochondria and Bioenergetics mentioning
confidence: 99%
“…Defective enzyme function(of dehydrogenases) in pathways of energy metabolism such as glycolysis, tricarboxylic acid pathway and electron transport chain have been well studied in AD progression. Defective PDH, KGDHC, cytochrome oxidase along with reduced activity of hexokinase, phosphofructokinase are the major enzymes reported in AD so far (87). In the paragraph below we will be further discuss some of these DHOs and their mechanism of metabolic dysfunction in AD.…”
Section: Metabolic Dysfunction and Its Link To Alzheimer's Disease: Tmentioning
confidence: 99%